Warning! This is not your typical mentor training: an invitation to explore a video-based mentor training to prepare mentor teachers for their roles in the classroom - Jamie Silverman; Michelle Pasko (School-University Partnerships)
Purpose – The purpose of this conceptual paper is to define and explore the roles of mentors, the responsibilities and even misconceptions of their position in partnership schools, the characteristics of effective mentors, the gaps that exist in current mentor training and the need for updated and forward-thinking flexible and accessible mentor training as it relates to improvements in University Teacher Preparation Programs and their partnership schools. Design/methodology/approach – The authors detail the process of interviewing a diverse population of mentors and teacher candidates (TCs) who have participated in our professional development (partnership) schools. See Appendices A and B for parallel questions posed during each interview process. Following the interviews, data were gathered in both text and video-based formats to create mentor training video modules to improve the current state of mentor training in our program. Themes were identified following an analysis of both interview intakes, and modules were created to align with these themes. Findings – Following the first rounds of implementation, the authors have reflected and noted that a need for an even more diverse population of both mentors and interns to be interviewed is necessary moving forward. The authors do note an appreciation by mentors and university partners in the quality, flexibility and accessibility that this new video module-based mentor training program provides. Practical implications – The video-based mentor training modules that the authors detail honor the needs of both new and returning mentors. Via the interviews with teacher candidates, mentors are able to empathize and understand how to be better mentors to their future TCs. Via the scenarios and questions that follow each thematically driven module, mentors are able to independently reflect on their current practices and ways to improve their roles. At any point in the internship year, mentors can return to the video training modules to review and thus improve their practice. Social implications – Mentors, university supervisors, teacher candidates and site coordinators (those individuals who identify mentors in their buildings) note improvement in their ability to communicate effectively as a result of being presented with video modules and reflections about the role of mentors from both mentors and TCs. Originality/value – The authors were called on by leadership in the College of Education at the University to create this original mentor training video module. It is unique to the College of Education at the University. Great value exists in its accessibility, adaptability (we can upload new videos at any time) and representation of both the mentor and TC perceptions, suggestions and experiences in our program.